Prostor, regija, razvoj - Polajnar Horvat, Katarina; Kavaš, Damjan; Nared, Janez; Razpotnik Visković, Nika (Regionalni razvoj, 2017)
The book Prostor, regija, razvoj ('Space, region, development') deals with numerous issues, relevant for regional policy and sustainable regional and spatial development. The fields addressed, like monitoring and evaluation, processes of urban development, situation on the real estate market, creative class, creative industry, cultural industry, and natural conditions as a factor of spatial and regional development, show the diversity and complexity of the processes taking place in space and regions. From this perspective our ambition is not to solve all the crucial issues at one time, but to contribute to spatial and regional policy with selected studies, methodological approaches and policy recommendations. The chapters pave the way to integrated spatial and regional development, bearing in mind complexity of the field and knowing the most recent analyses. In order to support decision-making with the adequate knowledge, comprehensive studies should be further supported and later used in the policy making processes.